Exploring Child Adoption Among Muslim Families in Lubuklinggau: A Maslahah Perspective and Islamic Legal Insights: Penelitian - Rajab Martadi Tanjung; Solina Balqis; Aida Rahmi Nasution (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study examines child adoption practices among Muslim families in Lubuklinggau, Indonesia, focusing on the interplay between sharia principles, national law, and socio-cultural dynamics. Using a Systematic Narrative Review approach, the research analyzes primary, secondary, and tertiary sources, including fiqh literature, legislation, and the illustrative case of Lubuklinggau Religious Court No. 55/Pdt.P/2024/PA.LLG. Findings indicate that the kafālah model predominates, providing care, education, and protection while preserving biological lineage (nasab). The study highlights the critical role of maslahah as a harmonizing framework, bridging gaps between religious obligations, legal requirements, and social expectations. Mechanisms such as hibah and wasiat wajibah ensure adopted children receive fair economic support without violating sharia principles. This research contributes conceptually by demonstrating the applicability of maslahah in contemporary Islamic family law and practically by offering guidance for Religious Court judges and policymakers in achieving the best interests of the child.